Shear resistance of sandwich panel connection at elevated temperature. (14th October 2021) - Cábová, Kamila; Garifullin, Marsel; Shoushtarian Mofrad, Ashkan; Wald, František; Mela, Kristo; Ciupack, Yvonne
Abstract : Purpose: Sandwich construction has developed and has become an integral part of lightweight construction. In the recent projects, it has been shown that by using sandwich panels as stabilizing members, a considerable amount of savings of steel can be achieved for structural members at ambient temperature. These stabilizing effects may also help to achieve similar savings in case of fire. Design/methodology/approach: The response of a sandwich single panel as well as the behaviour of the whole structure at ambient temperature and in case of fire is influenced by joints between the sandwich panels and the sub-structure. The fastenings used to fix the sandwich panels to a sub-structure may be loaded by shear forces caused by self-weight, live loads or diaphragm action. Therefore, an experimental investigation was conducted to investigate the shear behaviour of sandwich panel joints in fire. Findings: This paper summarized briefly the experimental results, numerical simulations and analytical models on the shear behaviour of sandwich panel joints at ambient and elevated temperatures. Research limitations/implications: The work is limited to studied types of screws and sandwich panels which are generally used in current sandwich construction. Practical implications: These stabilizing effects in sandwich construction help to achieve savings in case of fire. Social implications: Sandwich construction has developed and has become an integral part of lightweight construction. In the recent projects, it has been shown that by using sandwich panels as stabilizing members, a considerable amount of savings of steel can be achieved for structural members at ambient temperature. These stabilizing effects help to achieve similar savings in case of fire. Originality/value: This paper summarized briefly the experimental results, numerical simulations and analytical models on the shear behaviour of sandwich panel joints at ambient and elevated temperatures, which were not published yet.